MANAJEMEN AKOMODASI SYARIAH DI PULAU LOMBOK - Fatana Suastrini (Yayasan Nusantara Hasana Berdikari, 2023)
Halal tourism is a sector in the Islamic economy that is experiencing rapid development. Tourism development on Lombok Island still focuses on the development of natural and cultural tourism. The development of sharia tourism on the island of Lombok is not optimal. The tourism industry is of course very closely related to the accommodation business. Therefore, there is a need for a study on the potential management of sharia accommodation on Lombok Island, West Nusa Tenggara. This research is a descriptive research. According to the NTB MUI, the reason for the lack of sharia accommodation was triggered because many hotels were afraid that their guests would disappear after their hotels obtained the legality of a halal certificate. In fact, sharia accommodation is a very prospective potential in accordance with Lombok's branding as a Halal Tourism Destination. Sharia accommodation management needs to implement facilities and services, both physical and non-physical. Non-physical Islamic service standards, for example: dress etiquette, greeting greetings, congregational prayers for employees, and good and polite behavior when interacting between hotel managers and guests. Physical Islamic services, such as: facilities in guest rooms that provide Qibla direction, ablution facilities, prayer equipment, the Koran, and seats for those who are not muhrim. Apart from preparing several prayer facilities in the room, the room was also set to a size that almost matched the size of the Prophet's room. Other facilities that are of Islamic standard are swimming pool facilities. Swimming pools need to be separated between men's and women's pools. Sharia hotel accommodation restaurant facilities provide halal-standard food that has been certified by the Indonesian Ulema Council.